2001
DOI: 10.1137/s0097539799358847
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Buy-and-Hold Strategies for Financial Markets with Bounded Daily Returns

Abstract: In the context of investment analysis, we formulate an abstract online computing problem called a planning game and develop general tools for solving such a game. We then use the tools to investigate a practical buy-and-hold trading problem faced by long-term investors in stocks. We obtain the unique optimal static online algorithm for the problem and determine its exact competitive ratio. We also compare this algorithm with the popular dollar averaging strategy using actual market data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 16 publications
0
33
0
Order By: Relevance
“…The online search problem is very similar to that of the one-way trading problem [8,11,12]. In fact, one-way trading can be seen as randomized searching.…”
Section: Introductionmentioning
confidence: 99%
“…The online search problem is very similar to that of the one-way trading problem [8,11,12]. In fact, one-way trading can be seen as randomized searching.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Fujiwara et al [11] have studied the one-way trading problem under the assumption that the input prices follow some given probability distribution. In [8], Chen et al introduced the planning game problem, which is similar to the one-way trading problem, and they gave an algorithm for their problem which imposes some different constraint on the prices: instead of assuming that p i ∈ [m, M ] for some price range [m, M ], their algorithm assumes that the difference between any two consecutive prices p i and p i+1 is not too large, or more precisely, they assumed that for any i, p i /β ≤ p i+1 ≤ αp i for some fixed α, β > 1. They showed that if there are n buyers, their algorithm has competitive ratio nαβ−(n−1)(α+β)+(n−2) αβ−1 .…”
Section: Previous Resultsmentioning
confidence: 99%
“…yen) so as to maximize her final payoff while the price (or exchange rate from dollar to yen) varies unpredictably. There is a known simple transformation of (randomized) online search to (deterministic) one-way trading [2,[5][6][7]: The budget corresponds to probability 1 and exchanging some fraction of money (in deterministic one-way trading) means to stop the game with exactly that probability (in randomized online search) [5,7]. El-Yaniv et al suggested optimal solutions for several slight variants of the online search problem in which the upper/lower bounds of prices are constants and known a priori to the player [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Since the optimal solutions for these variants are quite simple computationally (that is, the amounts to exchange are easy to compute, but the analysis is quite sophisticated), practical issues can be transformed to online search in order to find optimal solutions [8][9][10]. Chen et al suggested another variant of the problem in which the next price r depends on the current price r in a geometric manner: r/θ ≤ r ≤ rθ , where θ > 1 is the daily fluctuation ratio [2]. For the variant, these authors presented closed-form solutions to the competitive ratio.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation